Three-dimensional MHD boundary layer flow due to an axisymmetric shrinking sheet with radiation, viscous dissipation and heat source/sink - Madhu, Macha; Balaswamy, B.; Kishan, Naikoti (Zielona Góra: Uniwersytet Zielonogórski)
An analysis is made to study a three dimensional MHD boundary layer flow and heat transfer due to a porousaxisymmetric shrinking sheet. The governing partial differential equations of momentum and energy aretransformed into self similar non-linear ordinary differential equations by using the suitable similarity transformations.
Keywords: axisymmetric shrinking sheet; dual solution; radiation; viscous dissipation; FEM